The Influence Of Accountability, Transparency And Supervision On Budget Performance At Higher Education Service Institutions (LLDIKTI) Region XIII Aceh - Ilyas, Eliana; Ivana, Farah; Mediyanti, Sisca; Ridha, Ainul; Masri (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2024)
This study aims to analyse the effect of accountability, transparency and supervision on budget performance at LLDIKTI Region XIII Aceh. This research is a type of causal associative research with a quantitative approach. The research sample was employees at LLDIKTI Region XIII Aceh, totalling 99 employees using the census technique. Accountability, Transparency and Supervision variables on budget performance are measured using a Likert scale, and data obtained by distributing questionnaires to respondents. Data analysis using statistical analysis of correlation and multiple regression models with the help of SPSS 25 software. To test each item on each variable, validity and reliability tests have been carried out as an instrument. The results of the analysis show that simultaneously there is an influence between Accountability, Transparency and Supervision on budget performance. The results of the F test obtained Fcount> Ftabel or (63.924> 2.70) and a significant test that the p value of 0.000 < p set at 0.05 which means significant. Partial test results show that: 1. Accountability affects budget performance with Thitung 4.791> Ttabel 1.660 and p value 0.000 < p 0.05 means significant. 2. Transparency affects budget performance with Thitung 5,263> Ttabel 1,660 with a p value of 0.000 from <0.05 means significant. 3. Supervision affects budget performance with Thitung 2.968> Ttabel 1.660 with a p value of 0.002 from <0.05 means significant.